Neoadjuvant tislelizumab and tegafur/gimeracil/octeracil (S-1) plus oxaliplatin in patients with locally advanced gastric or gastroesophageal junction cancer: Early results of a phase 2, single-arm trial - Yin, Yuping; Lin, Yao; Yang, Ming; Lv, Jianbo; Liu, Jiaying; Wu, Ke; Liu, Ke; Li, Anshu; Shuai, Xiaoming; Cai, Kailin; Wang, Zheng; Wang, Guobin; et al. (Frontiers in Oncology, 2022)
Background Recently combination of immunotherapy with chemotherapy has been recommended as first line treatment of metastatic gastric/gastroesophageal junction (G/GEJ) in clinical guidelines of many countries, the therapeutic potential of this application need to be further investigated in neoadjuvant therapy of advanced G/GEJ cancer patient. Methods We performed a prospective, single-arm, open-label, phase 2 trials of PD-1 inhibitor Tislelizumab combined with S-1 plus Oxaliplatin (SOX) in patients with advanced LAG/GEJ cancer. All patients performed 3-cycles (21 days /1 cycle) treatment except for 1 patient performed 2-cycles. The primary endpoints were tumor major pathology response (MPR) and other events of tumor response assessed by RECIST 1.1 and Becker criteria. Besides, we constructed a few-shot learning model to predict the probability of MPR which could screen those patients who might be benefited from neoadjuvant immunotherapy-chemo scheme. This study was registered at https://clinicaltrials.gov/ct2/show/NCT0-4890392. Findings Thirty-two patient were enrolled, 17 patients (53.1%) achieved MPR (≤ 10% viable tumor cells) after treatment and 8 among them (25.0%) had a pathological complete response (pCR). The 1-year overall survival (OS) rate was 91.4% and the 1-year Recurrence-free survival (RFS) rate was 90.0%. Adverse events occurred in 24 patients (65.6%) and grade III-IV adverse event were observed in 4 patients (12.5%) during neoadjuvant period. Besides, we found commonly-used preoperative assessment tools such as CT and EUS presented limited accuracy of tumor therapeutic response in this study, thus we developed a therapeutic response predictive model which was consisted of TNFα, IFNγ, IL-10, CD4 and age of patient, and the AUC of this FSL-model were 0.856 (95%CI:0.823-0.884). Interpretation Our study showed neoadjuvant PD-1 Inhibitor Tislelizumab combined with SOX had promising application potential and presented no-increasing treatment-related adverse events in patients with advanced G/GEJ cancer. Moreover, the predictive model could help therapists to evaluate the therapeutic response of this scheme accurately